Optimasi Biaya Distribusi pada UMKM Produsen Keripik Pisang Lokal melalui Model Transportasi Menggunakan LINGO - Yelita Anggiane Iskandar; Herry Kartika Gandhi; Alyaa Aina Azzahra; Sava Aulia Atthaya; Aulia Nisa Ramadani; Nur Ekha Azka Rasidah; Rexalis Athaya Putri (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
Distribution is one of the key activities in the operations of Micro, Small, and Medium Enterprises(MSMEs) because it directly affects operational costs and business competitiveness. SomeMSMEs, such as Dapur Mama, still determine distribution patterns based on habitual practiceswithout quantitative calculations, which may lead to cost inefficiencies. This study aims to optimizethe distribution cost of Keripik Pisang Jawara products using a transportation model approach.The method applied is Integer Linear Programming (ILP), solved with the assistance of LINGOsoftware. Research data were obtained through interviews with the MSME management, includingwarehouse capacity, demand at each destination, and unit distribution costs. The results show thatthe transportation model can determine an optimal distribution pattern that minimizes totaldistribution costs without violating capacity and demand constraints. The optimal solution yieldsa minimum total distribution cost of 20,940 cost units. Therefore, the ILP-based transportationmodel is proven effective in improving distribution cost efficiency and can serve as a decisionsupporttool for MSMEs.